Computational neurostimulation - Bestmann, Sven (Progress in brain research, 2015)
Computational Neurostimulation, the latest volume in the Progress in Brain Research series provides an introduction to a nascent field with contributions from leading researchers. In addition, it addresses a very timely and relevant issue which has long been known to require more treatment.